2020
DOI: 10.1590/0034-7167-2019-0236
|View full text |Cite
|
Sign up to set email alerts
|

Homeless population: characterization and contextualization by census research

Abstract: Objectives: to analyze characteristics of homeless people and factors associated with living on the streets. Methods: a census-type sectional survey carried out between 2015 and 2018, in the municipality of Maringá-Paraná. A total of 701 homeless answered a structured questionnaire with sociodemographic data, living conditions, and drug use. We used Pearson’s correlation test for the association analysis of the variables at a 95% confidence level. Results: men (90.7%) the average age of 37.7 years had been h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 16 publications
5
12
1
5
Order By: Relevance
“…In agreement with previous published Brazilian data [11][12][13][14][15][16], the studied population is composed predominantly of single and heterosexual men, with an average age of 30 to 40 years old. However, a irst divergence observed in our study was ethnicity, which attributed a predominance of whites, in disparity of most studies found in the literature [11,13,14,[16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement with previous published Brazilian data [11][12][13][14][15][16], the studied population is composed predominantly of single and heterosexual men, with an average age of 30 to 40 years old. However, a irst divergence observed in our study was ethnicity, which attributed a predominance of whites, in disparity of most studies found in the literature [11,13,14,[16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous published Brazilian data [11][12][13][14][15][16], the studied population is composed predominantly of single and heterosexual men, with an average age of 30 to 40 years old. However, a irst divergence observed in our study was ethnicity, which attributed a predominance of whites, in disparity of most studies found in the literature [11,13,14,[16][17][18][19]. This discrepancy is probably due to the ethnic diversity of the locations considered and the few samples of this population in some studies, such as a study about the Brazilian Midwest region [19], with 43 individuals, and another about the South region [18], with only ten.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations